Micro and Nanoscale Technologies for Diagnosis of Viral Infections. Issue 45 (26th July 2021) - Nasrollahi, Fatemeh; Haghniaz, Reihaneh; Hosseini, Vahid; Davoodi, Elham; Mahmoodi, Mahboobeh; Karamikamkar, Solmaz; Darabi, Mohammad Ali; Zhu, Yangzhi; Lee, Junmin; Diltemiz, Sibel Emir; Montazerian, Hossein; Sangabathuni, Sivakoti; et al.
Abstract: Viral infection is one of the leading causes of mortality worldwide. The growth of globalization significantly increases the risk of virus spreading, making it a global threat to future public health. In particular, the ongoing coronavirus disease 2019 (COVID‐19) pandemic outbreak emphasizes the importance of devices and methods for rapid, sensitive, and cost‐effective diagnosis of viral infections in the early stages by which their quick and global spread can be controlled. Micro and nanoscale technologies have attracted tremendous attention in recent years for a variety of medical and biological applications, especially in developing diagnostic platforms for rapid and accurate detection of viral diseases. This review addresses advances of microneedles, microchip‐based integrated platforms, and nano‐ and microparticles for sampling, sample processing, enrichment, amplification, and detection of viral particles and antigens related to the diagnosis of viral diseases. Additionally, methods for the fabrication of microchip‐based devices and commercially used devices are described. Finally, challenges and prospects on the development of micro and nanotechnologies for the early diagnosis of viral diseases are highlighted. Abstract : Viral infections are the leading causes of mortality worldwide. Micro and nanoscale technologies have been used to develop diagnostic platforms for rapid and accurate detection of viral diseases. Here, these technologies are reviewed for sampling, sample processing, enrichment, amplification, and detection of viral particles and antigens. Challenges and future directions in this area are highlighted.